2005
DOI: 10.1016/j.eurpsy.2004.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and olanzapine plasma levels in acute schizophrenia

Abstract: Olanzapine plasma level determination seems to be a useful tool in optimizing acute treatment particularly for more problematic cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 28 publications
4
38
0
1
Order By: Relevance
“…This is a limitation of our study, and plasma levels for both ziprasidone and olanzapine were rather low but can still be considered to reach a clinical effective range (Perry et al, 1997;Daniel et al, 1999;Miceli et al, 2000;Mauri et al, 2005). Despite the fact that the doses for olanzapine and ziprasidone are not entirely equivalent in their D(dopamine) 2 blocking ability, it is not likely that D 2 effects account for the results observed.…”
Section: Discussionmentioning
confidence: 79%
“…This is a limitation of our study, and plasma levels for both ziprasidone and olanzapine were rather low but can still be considered to reach a clinical effective range (Perry et al, 1997;Daniel et al, 1999;Miceli et al, 2000;Mauri et al, 2005). Despite the fact that the doses for olanzapine and ziprasidone are not entirely equivalent in their D(dopamine) 2 blocking ability, it is not likely that D 2 effects account for the results observed.…”
Section: Discussionmentioning
confidence: 79%
“…There was no significant improvement in negative symptoms (as evaluated by means of PANSSn) in either group during this shortterm study, thus confirming that, as in the case of other antipsychotics, more time is required to detect a significant improvement in negative symptoms such as blunted affect, emotional withdrawal, or poverty of speech. 19 However, it is worth noting the greater variability in clinical responses in the group of patients treated at low starting and maintenance doses; furthermore, the higher doses seemed to be more effective on anxiety and suspiciousness. The more rapid and effective management of these clinical dimensions is an important goal in the treatment of critical periods of acute psychosis, especially in a psychiatric ward.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study found a positive curvilinear relationship between plasma OLZ levels and clinical improvement; 19 and, because plasma OLZ levels were also positively related to oral OLZ doses, it can be argued that intermediate dosages of 10 to 20 mg/d are responsible for the better clinical response. However, the present study found no significant differences in clinical efficacy between the patients treated with the lower and high doses, although it must be pointed out that the finding of only a trend toward higher plasma levels in the group treated with the higher doses was probably because of the high degree of interindividual variability in plasma OLZ levels, as has also been reported in the case of other antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Perry et al suggested that a minimum concentration of 23 ng/ml was needed to be effective, but did not draw any link with improvements in BPRS scores [14]. Mauri et al described a curvilinear relationship with clinical efficacy between 20 and 50 ng/ml of olanzapine serum concentration [15]. Lane et al, however, failed to establish any correlation between olanzapine blood level and improvements in schizophrenic symptoms, although they did find one for depressive symptoms, with a plasma concentration of 36 ng/ml being a good predictor of response [16].…”
Section: Discussionmentioning
confidence: 99%